Population change, labor markets and sustainable growth towards a new economic paradigm - Mason, Andrew, 1947-; Yamaguchi, Mitoshi (Emerald, 2007)
Birth rates are dropping to ever-lower levels around the world. Populations are growing more slowly and, in some cases, beginning to decline. Rapid population aging has begun in the West and parts of Asia and is just over the horizon elsewhere. The demographic changes, their economic implications, and possible policy responses are the subject matter of this volume. What will be the effects on economic performance? How can couples be encouraged to marry and have children? Can educational reform lead to a more productive young labor force helping to offset their meager numbers? Can labor market reform extend the work life of older workers without damaging the interests of others? How should the social safety net that supports the elderly evolve in ways that are both fair and sustainable? The papers in this volume draw on international experience to address these issues, but emphasize the experience of Japan the country with the worlds oldest population. It includes contributors such as: Noriko Aoki, Akira Kawaguchi, Allen Kelley, Wei Huang, Robert Hutchens, Tomoko Kinugasa, Andrew Mason, Naoki Mitani, Takashi Oshio, Robert Schmidt, and Mitoshi Yamaguchi.
Includes index.
Keywords: Sustainable development.; Labor economics.; elektronické knihy; electronic books